Dos interpretaciones humanísticas de un tópico clásico: el poema a la muerte de un ave (y II): la "Deploratio sturni" de Giovanni Pontano - Díaz Gito, Manuel Antonio (2002)
The aim of this study is the analysis of the different treatment of a well-known classical topic in the tradition of the Roman erotic poetry, the poem to the death of a pet-bird, by two representative Italian humanists of the Quattrocento, Maffeo Vegio and Giovanni Pontano. In this paper we present the second part of this study focused on the Deploratio sturni (De tumulis 2,51) by Giovanni Pontano.
Keywords: Pontano, Giovanni Gioviano, -- 1426-1503; Poesía; Crítica literaria; Humanistas